2005
DOI: 10.1085/jgp.200409212
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Phosphatase Activity, Increased Ca2+ Sensitivity, and Myosin Light Chain Phosphorylation in Urinary Bladder Smooth Muscle of Newborn Mice

Abstract: Developmental changes in the regulation of smooth muscle contraction were examined in urinary bladder smooth muscle from mice. Maximal active stress was lower in newborn tissue compared with adult, and it was correlated with a lower content of actin and myosin. Sensitivity to extracellular Ca2+ during high-K+ contraction, was higher in newborn compared with 3-wk-old and adult bladder strips. Concentrations at half maximal tension (EC50) were 0.57 ± 0.01, 1.14 ± 0.12, and 1.31 ± 0.08 mM. Force of the newborn ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 27 publications
9
42
0
Order By: Relevance
“…Consistent with previous studies with different neonatal SMs (8,9,11,12,14,31), we found that actin and myosin expression and specific active peak force elicited by KCl and carbachol at optimal length were lower compared with the adult. Specific force takes into account that the mechanical output depends on multiple factors, some of which are difficult to assess.…”
Section: Excitation Contraction Coupling In Relation To Contractile Psupporting
confidence: 92%
“…Consistent with previous studies with different neonatal SMs (8,9,11,12,14,31), we found that actin and myosin expression and specific active peak force elicited by KCl and carbachol at optimal length were lower compared with the adult. Specific force takes into account that the mechanical output depends on multiple factors, some of which are difficult to assess.…”
Section: Excitation Contraction Coupling In Relation To Contractile Psupporting
confidence: 92%
“…In support of this hypothesis, contractions produced by bladder from newborn mice that express predominantly nonmuscle myosin II, but not adult mice that express predominantly smooth muscle myosin II, are inhibited by 10 M (Ϫ)blebbistatin (Ekman et al, 2005). In contrast, Rhee et al (2006) recently showed that tonic contractions of adult mouse aorta and bladder are inhibited by (Ϫ)blebbistatin, and based on data suggesting that blebbistatin is selective for inhibition of nonmuscle over smooth muscle myosin II (Limouze et al, 2004), these authors concluded that tonic contractions are dependent on nonmuscle myosin.…”
Section: Discussionmentioning
confidence: 87%
“…Tonic force maintenance has been attributed to nonmuscle myosin II (Morano, 2003;Limouze et al, 2004;Ekman et al, 2005). We therefore examined the relative expression of smooth and nonmuscle myosin II in rabbit renal, femoral, and saphenous arteries and chicken carotid artery and gizzard.…”
Section: Blebbistatin Inhibits Arterial Contraction and Myosin Atpasementioning
confidence: 99%
“…In the present study we documented that the fetal and newborn pulmonary arterial tissue has a lower MYPT content when compared with the adult. The rate of MLCP-induced relaxation has been shown to be dependent on the MYPT content and is lowest in the newborn mice bladder smooth muscle (13), suggesting that a similar mechanism may be operative in the pulmonary vascular tissue.…”
Section: Discussionmentioning
confidence: 99%